Multibreath alveolar oxygen tension imaging. Issue 4 (15th October 2015) - Clapp, Justin; Hamedani, Hooman; Kadlecek, Stephen; Xin, Yi; Shaghaghi, Hoora; Siddiqui, Sarmad; Rossman, Milton D.; Rizi, Rahim R.
Abstract : Purpose: This study tested the ability of a multibreath hyperpolarized HP 3 He MRI protocol to increase the accuracy of regional alveolar oxygen tension ( P A O2 ) measurements by lessening the influence of gas‐flow artifacts. Conventional single‐breath P A O2 measurement has been susceptible to error induced by intervoxel gas flow, particularly when used to study subjects with moderate‐to‐severe chronic obstructive pulmonary disease (COPD). Methods: Both single‐breath and multibreath PA O2 imaging schemes were implemented in seven human subjects (one healthy, three asymptomatic smokers, and three COPD). The number and location of voxels with nonphysiologic P A O2 values generated by intervoxel gas flow were compared between the two protocols. Results: The multibreath scheme resulted in a significantly lower total percentage of nonphysiologic P A O2 values (6.0%) than the single‐breath scheme (13.7%) ( P = 0.006). P A O2 maps showed several patterns of gas‐flow artifacts that were present in the single‐breath protocol but mitigated by the multibreath approach. Multibreath imaging also allowed for the analysis of slow‐filling areas that presented no signal after a single breath. Conclusion: A multibreath approach enhances the accuracy and completeness of noninvasive P A O2 measurement by significantly lessening the proportion of nonphysiologic values generated by intervoxel gas flow. Magn Reson Med 76:1092–1101, 2016. © 2015 Wiley Periodicals, Inc.